Pengaruh metode pembelajaran make-a match (mencari pasangan) dan metode role playing terhadap hasil belajar ipa-biologi pada siswa kelas viii smp muhammadiyah 1 surakarta semester genapTahun ajaran 2015/2016 - Yariyani, Lina; , Dr. Sofyan Anif M.Si (2016)
The aims of this research is to know the influence using "make a match" method with "role playing" method to the learning outcome of IPA Biology on main discussion "Struktur dan Fungsi Jaringan Tumbuhan" students at VIII class in SMP Muhammadiyah 1 Surakarta of even semester in 2015/2016 academic year. The type of this research is descriptive quantitative approach which is done by "true experiment". The population of this research are the students of VIII class of even semester which consist of five classes in SMP Muhammadiyah 1 Surakarta in 2015/2016 academic year. The sample of this research are three classes. The taking of sample is done using "stratifaid sampling" technique. The technique of collecting data are observation, documentation, and test. The technique of analysis data is one way variant analysis, before doing prerequite test of normality and homogeneity. The result of this research are F count in the amount of 83,431 with F table gained from the value of table F on significant level 5% with (db1 = 2) and (db2 = 79) is F table in the amount of 3.11. so, F count (83,431) > Ftabel (3,11), then Ho refused. It means that there are the diferrences of average student learning outcome. And then, it does continuity test (Pos Hok Test) the final result show that there are difference of using method role playing and make a match the learning outcomes in biology are learning to use make a match method is the best.